Quality Comparison of Meatball Made from Switches of Yellow Fin Tuna (Thunnus sp.) and Indian Scad (Decapterus russelli) With Addition of Carrots - Ayu, Lastri Sri; Setha, B.; Loppies, C. R. M. (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This study aims to determine the comparison of the quality of meatballs from switches of yellowfin tuna (Thunnus albacares) and Indian scad (Decapterus russelli) with the addition of carrots. The research was conducted in July 2022 at the Pattimura University FMIPA Laboratory. This study used proximate tests (moisture, ash, protein, and crude fiber), organoleptic tests, and bite tests. Data analysis was performed using the T-test and the Mann-Whitney test. The results showed that the T-test showed that only the protein content of Indian scad meatballs was significantly different from that of tuna meatballs, while the water content, ash content, and crude fiber content were not significantly different. In the Mann-Whitney test, the Indian scad meatball bite test was significantly different from tuna fish meatballs, while the appearance, smell, taste, and texture values were not significantly different.